Polishing of tungsten carbide by combination of anodizing and silica slurry polishing - Deng, Hui (2019)
Sintered tungsten carbide (WC) is widely used in precision molding of optical glass lenses, and is considered as a critical mold material for optical industry, due to its high hot hardness and low thermal expansion ratio. However, WC is also a well-known difficult-to-polish material owing to its high hardness and strong chemical inertness. In an effort to realize the high-quality and highly efficient polishing of WC, a two-step polishing process combining anodizing and soft abrasive polishing was developed. Experimental studies of the anodizing step and the slurry polishing step were conducted. Anodizing has been found to be able to quickly soften WC and realized a drastic decrease of its surface hardness from 22.1 GPa to below 2.0 GPa, which allows us to polish the substrate surface using soft silica abrasives. In the polishing step using silica slurry, the oxide layer was removed and it has been revealed that the surface quality of polished WC was greatly affected by the duration of anodizing and the type of polishing pad. A scratch-free, pit-free and smooth WC surface can be obtained by combination of 10 min of anodizing and 30 min of silica slurry polishing using a suede type polishing pad. This research offers a new method for achieving high-quality finishing of WC with high efficiency.